(untitled) (Singaporean Journal of Business Economics and Management, 2014)
In our modern environment today, organization operates dynamically where people are concerned with stress. Work-related stress can affect individuals when they feel an inability to cope or control demands placed on them within their work environment which can eventually contribute to the development of maladaptive behavours such as drinking and smoking and health conditions such as depression, anxiety, nervousness, fatigue and heart disorder (European Agency for Safety and Health at Work (EASHW), 2002). Over the last few years the issues of stress have attained greater prominence. Within a work environment, stress can be a cause as well as an effect of violence. According to Smith et al, (1999) who in their research indicated that one third of the working population in developed countries report high to very high levels of stress. Similarly, evidence from newly industrialized countries also showed indicative of the prevalence of stress. Time pressures, excessive demands, role conflicts, ergonomic deficiencies, job security and relationship with customers are particularly common stressors amongst employees in the financial services (Grace & Icompier, 1999). Furthermore, new stressors such as computer breakdowns, computer slowdowns and electronic performance monitoring, have developed as a result of increased human interaction with computers.